The Impact of Dynamic Land-Use and Spatial Planning Policies on the Traditional Village and Architecture in Tourism Villages in Gianyar, Bali - I Dewa Gede Agung Diasana Putra (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Tourism and community participation have transformed the physical setting of the traditional Balinese villages in various directions. Tourism village is an important type of spatial planning policies in Bali that focus on cultural tourism. In cultural tourism, the traditional villages including cultural and traditional practices of the people are the main resources of tourist activities. Therefore, the traditional village pattern and land use are signif icant in tourism development. Through integrating participatory rural appraisal (PRA) methods with land use and architectural-historical investigation, this paper explores and investigates the spatial pattern of land use transformation in tourism villages. The results indicate that tourism villages in Gianyar have experienced an expansion in both the horizontal and vertical dimensions, with increasing land intensity. This expansion was accompanied by the touristif ication process, with land use changing from addressing villagers’ needs to satisfying tourists’ demands. However, this paper states that the transformation is read as a pragmatic response to address new challenges in the community by interpreting the reconf iguration of the villages and houses.